1950
DOI: 10.1002/jsfa.2740010205
|View full text |Cite
|
Sign up to set email alerts
|

The component acids and glycerides of dika fat

Abstract: The component fatty acids of a West African dika fat were found to be capric 1.6, lauric 43.0, myristic 46.4, palmitic 6.2, oleic 2‐6, linoleic 0.2% (wt.). Exhaustive crystallization of a portion of the fat failed to resolve it into any one individual triglyceride fraction. The chief component glycerides present were found to be trilaurin 7.1, myristodilaurin 32‐5, caprolauro‐myristin 5.2, lauromyristopalmitin 13.1, laurodimyristin 28.7, trimyristin 5.1, and oleolauromyristin 5.1%. The experimental evidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1953
1953
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Post-harvest losses due to senescent deterioration, pests and diseases are considerable because of poor handling practices and lack of storage facilities. Although there are some reports on the chemical composition and nutritive value of wild mango seeds (Meara & Patel, 1950;Abaelu & Akinrimisi, 1980;Eka, 1980), there is little information on the composition, respiration or quality of edible wild mango fruits during ripening. This study was intended to provide such information to improve effective handling and methods of storage to extend the shelf-life of the fruit and improve its commercial utilization.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Post-harvest losses due to senescent deterioration, pests and diseases are considerable because of poor handling practices and lack of storage facilities. Although there are some reports on the chemical composition and nutritive value of wild mango seeds (Meara & Patel, 1950;Abaelu & Akinrimisi, 1980;Eka, 1980), there is little information on the composition, respiration or quality of edible wild mango fruits during ripening. This study was intended to provide such information to improve effective handling and methods of storage to extend the shelf-life of the fruit and improve its commercial utilization.…”
Section: Introductionmentioning
confidence: 97%
“…The other bears fruits with bitter, very fibrous inedible pulp surrounding an endocarp containing two large, flat, whitish cotyledons that, after sun drying and milling, are used in soups as a flavouring ingredient and to impart desired consistency, because of their stringy, gum-like properties. The oil-rich seeds are also used for the preparation of dika fat (Meara & Patel, 1950).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, TAGs were only identified based on authentic standards without further quantitation. Meara & Patel () have determined TAG proportions in fractions of crystallised kernel fat, reporting similar proportions of LaLaM (32.5%), LaMM (28.7%), LaMP (13.1%), and MMM (5.1%) compared to our samples. They have further identified the trisaturated CLaM in the crystallised fractions of the fat.…”
Section: Resultsmentioning
confidence: 99%
“…Dika wax is an edible vegetable fat derived from the kernel of Irvingia gabonensis Var excelcia (Ofoefule et al, 1997;Okorie, 2000), with melting point range of 38 C to 41 C (Meara and Patel, 2006). Soybean oil is also edible oil from Glycine soja and is one of the most important bean sources in the world, providing vegetable protein and oil for millions of people and supplying important functional ingredients to the food, health care, pharmaceutical and chemical industries (Liu, 1999).…”
Section: Introductionmentioning
confidence: 99%